The Concordance between Teachers' and Parents' Perceptions of School Transition Practices: A Solid Base for the Future. Issue 2 (3rd March 2016) - Ahtola, Annarilla; Björn, Piia Maria; Turunen, Tiina; Poikonen, Pirjo-Liisa; Kontoniemi, Marita; Lerkkanen, Marja-Kristiina; Nurmi, Jari-Erik
Abstract : This study focuses on parents' and teachers' perceptions of practices aimed at easing the transition to formal schooling (e.g., familiarization with the school, discussions about the school entrants). A total of 230 preschool teachers, 131 elementary school teachers, and 2, 662 mothers and fathers filled in a questionnaire containing items on how important they considered different preschool-school transition practices. The participants considered the various transition practices to be at least somewhat important. On average, familiarization with the school was considered to be most important, whereas teacher co-operation and joint writing of curricula were considered to be least important. The perceptions of the participant groups differed from each other significantly in almost all practices. We suggest that the information on school entrants should be transferred within joint meetings between transition partners and other professionals whenever possible.